Implementation of the Tahsin Al-Qur'an Program Using the Talaqqi Method for the Community of Nagari Durian Tinggi, Kapur IX District, Lima Puluh Kota Regency, West Sumatra - Muhammad Iqbal; Putri Larasia (ASSUNNAH PRESS, 2025)
This study examines the implementation of a community service program based on Participatory Action Research (PAR) in the form of Tahsin Al-Qur'an using the Talaqqi method in Nagari Durian Tinggi, Kapur IX District, Lima Puluh Kota Regency. Through a reflection-action-reflection cycle, this service involves the community as active partners, not objects, in identifying, addressing, and evaluating Qur'anic literacy issues. Initial results showed that 87% of participants experienced difficulties in applying tajwid and makhrajil huruf. Collaborative intervention for 14 days with 5 participants resulted in significant improvements in three main components: makharijul huruf (103.8%), basic tajwid (123.8%), and reading fluency (53.0%). The final reflection cycle demonstrated social transformation in the form of established sustainable learning systems, the emergence of local leaders, and the development of collective commitment to Qur'anic literacy. This study produced a partnership-based empowerment model that can be replicated in similar contexts to improve Qur'anic literacy in rural communities.